PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA DESA DAN PDRB TERHADAP KEMISKINAN - Ramadhina, Siti; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2024)
This study aims to determine the effect of DAU, DAK, Village Fund and GRDP on Poverty in West Java Province in 2018-2022. This study used a quantitative approach. Data analysis uses panel data regression analysis which is a combination of 2018-2022 time series data and crosssection data of 16 districts in West Java Province. The results showed that DAU, DAK, and GRDP had a negative and significant effect on poverty. When there is an increase in DAU, DAK and GRDP, it can reduce the number of poverty in West Java Province. Meanwhile, the Village Fund has a positive and significant effect on poverty. If there is an increase in the budget in the Village Fund, it will not affect the amount of poverty in West Java Province.